Iceland : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In this study, during 2008, the financial crisis lead Iceland's public debt to soar from under 30 percent of GDP to more than 100 percent of GDP, and while underlying external debt came down sharply, it remains elevated at close to 300 percent of GDP. First, external sustainability is overviewed, and second, growth of Iceland's economy has been challenged, and finally, fiscal adjustments and its macroeconomic impacts are overviewed. Traditional external debt sustainability analysis (DSA) suggests that Iceland's external debt is sustainable but is vulnerable to depreciation shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet